1988
DOI: 10.1123/ijsb.4.4.315
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Lower Limb Muscle Function in Ergometer Rowing

Abstract: In an effort to seek further understanding of lower limb muscle function in the rowing movement, an electromyographic analysis was undertaken of rowers rowing on a Gjessing ergometer. A strain gauged transducer was inserted in the ergometer linkage between handle and flywheel to detect pulling force. Electrodes were placed on the following lower limb muscles: gluteus maximus, biceps femoris, rectus femoris, vastus lateralis, gastrocnemius, and tibialis anterior. Linear envelope electromyograms from each muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
13
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 7 publications
7
13
0
Order By: Relevance
“…The synergy analysis, which extracts the underlying structure of the activations (patterns of co-variation among multiple muscles), also showed a large consistency across the three power outputs for both populations. Individual EMG patterns reported in the present study are in agreement with EMG patterns reported in the literature (Guével et al 2011;Lay et al 2002;Pollock et al 2009;Rodriguez et al 1990;Wilson et al 1988). However, these previous studies recorded a limited number of muscles (up to 12 muscles).…”
Section: Discussionsupporting
confidence: 95%
See 2 more Smart Citations
“…The synergy analysis, which extracts the underlying structure of the activations (patterns of co-variation among multiple muscles), also showed a large consistency across the three power outputs for both populations. Individual EMG patterns reported in the present study are in agreement with EMG patterns reported in the literature (Guével et al 2011;Lay et al 2002;Pollock et al 2009;Rodriguez et al 1990;Wilson et al 1988). However, these previous studies recorded a limited number of muscles (up to 12 muscles).…”
Section: Discussionsupporting
confidence: 95%
“…2 shows that this synergy had a time course roughly similar to Fx, i.e., the horizontal component of the footstretcher forces. This confirms previous observations highlighting the major functional role of the knee extensors to produce power on a rowing ergometer (Rodriguez et al 1990;Wilson et al 1988). Synergy #2 engaged the action of both the arm and trunk muscles.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This would have caused a low correlation between force and sum-iEMG. The muscles measured have, however, been reported to be among the most essential ones in rowing (Balle et al 1983;Wilson et al 1988). We believe that despite this above-mentioned handicap, the method used made it possible to study the eects of F I O 2 on force production and muscle electrical activity during severe exercise.…”
Section: Discussionmentioning
confidence: 93%
“…A similar method has been widely used in ergometer rowing (e.g. Wilson et al 1988). The range of the knee joint movement was monitored by an electrical goniometer attached to the medial side of the right knee.…”
Section: Exercise Designmentioning
confidence: 98%